Year-round slow cooker : 100 favorite recipes for every season - Cheney, Dina (Taunton Press, 2013)
"Slow cookers are popular for good reason: They're the ultimate kitchen problem solvers. If you're watching your budget, they're well worth the $30 they cost since they can turn the cheapest cuts of meat into unctuous, mouth-watering results worthy of a five-star restaurant. Slow cookers also do the hard work, cooking for hours while you're out of the house only to come home to a meal just about ready to eat. And since slow cookers keep food warm, they allow different family members to eat at different times: a practical option in a world of staggered schedules. Yet, slow cookers have an image problem. Most home cooks use them for cold weather meals only, while others think slow cookers can only produce food that's mushy, bland, and watery or rely solely on shortcut ingredients like spice packets, bouillon cubes, and bottled sauces. No longer does this must-have kitchen tool deserve to be stored away when spring months hit. In Year-Round Slow Cooker, home cooks will find 100 delicious, modern, practical slow cooker recipes featuring seasonal produce. Recipes speak to the home cook whose palate is more sophisticated and who wants to incorporate seasonal produce into all of her meals. Organized by season, Year-Round Slow Cooker features notes about the featured seasonal ingredients as well as invaluable tips throughout to help cooks maximize the power of the slow cooker"--